2013
DOI: 10.1891/0886-6708.11-043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Overlap of Childhood and Adult Physical, Sexual, and Emotional Abuse: A Descriptive Analysis of Results From the Boston Area Community Health (BACH) Survey

Abstract: Abuse is associated with a wide variety of health problems, yet comprehensive population-based data are scant. Existing literature focuses on a single type of abuse, population, or lifestage. Using a racially/ethnically diverse community-based sample, we document the prevalence of physical, emotional, and sexual abuse by lifestage and gender; assess variation in abuse by socio-demographics; establish overlap of abuses; and examine childhood abuse relationships with abuse in adulthood. Prevalence of abuse range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 47 publications
3
53
5
Order By: Relevance
“…Previous victims of SA experience a two to three fold increased risk of being re-victimized compared to those without a history of abuse 5 ; a finding that has generalized across college 6,7 , clinical 8,9 , and community-based samples 10,11,12 . Furthermore, risk of revictimization has been demonstrated via both retrospective and prospective research designs 11 .…”
mentioning
confidence: 94%
“…Previous victims of SA experience a two to three fold increased risk of being re-victimized compared to those without a history of abuse 5 ; a finding that has generalized across college 6,7 , clinical 8,9 , and community-based samples 10,11,12 . Furthermore, risk of revictimization has been demonstrated via both retrospective and prospective research designs 11 .…”
mentioning
confidence: 94%
“…Some studies have shown that people who have experienced physical and sexual abuse are more likely to be exposed to the same types of abuse in adulthood (Alexander, 2009;Chiu et al, 2013;Coid et al, 2001;Irwin, 1999;Stein et al, 2002). However, the re-victimization of individuals who have experienced emotional abuse and its effect on suicidality has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the proportion of respondents who experienced sexual abuse was higher among respondents who had experienced emotional abuse in childhood, suggesting that emotional abuse may co-occur with other forms of childhood abuse (Chiu et al, 2013).…”
Section: Sample Characteristics and T-testmentioning
confidence: 99%
See 2 more Smart Citations